Experiential learning not enough for organ procurement surgery: implications for perioperative nursing education - Smith, Zaneta; Leslie, Gavin; Wynaden, Dianne (NATCO-ORGANIZATION TRANSPLANT PROFESSIONALS, 2015)
Context —Perioperative nurses play a vital role in assisting in surgical procedures for multiorgan procurement, receiving little education apart from on-the-job experiential learning when they are asked to participate in these procedures. Objectives —Within an Australian context and as part of a larger study, this article describes issues that hindered perioperative nurses’ participatory experiences as a result of lacking education, previous exposure, and preparation for assisting in surgical procedures for organ procurement. Design —The grounded theory method was used to develop a substantive theory of perioperative nurses’ experiences of participating in surgical procedures for multiorgan procurement. Participants —Thirty-five perioperative nurses who had experience in surgical procedures for organ procurement from regional, rural, and metropolitan hospitals of 2 Australian states, New South Wales and Western Australia, participated in the research. Results —Levels of knowledge and experience emerged from the data as an influencing condition and was reported to affect the perioperative nurses’ participatory experiences when assisting in procurement surgical procedures. Six components of levels of knowledge and experience were identified and are described. Conclusion —The findings from this study provide a unique contribution to the existing literature by providing an in-depth understanding of the educational needs of perioperative nurses in order to assist successfully in multiorgan procurement procedures. These findings could guide further research with implications for clinical initiatives or education programs specifically targeting the perioperative nursing profession both locally and internationally.